2002
DOI: 10.1007/s10350-004-6139-7
|View full text |Cite
|
Sign up to set email alerts
|

Normal Female Anal Sphincter

Abstract: The female sphincter has a variable natural defect occurring along its anterior length. This makes interpretation of the isolated endoanal ultrasound difficult and explains previous overreporting of obstetric sphincter defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…The underlying reason for this is not clear. Some previous studies on normal female subjects did not show any association of IAS length with age and reproductive history[24,25]. However, the situation in CP is unclear.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The underlying reason for this is not clear. Some previous studies on normal female subjects did not show any association of IAS length with age and reproductive history[24,25]. However, the situation in CP is unclear.…”
Section: Discussionmentioning
confidence: 86%
“…Several studies have shown that IAS thickness is a more reliable and reproducible parameter than EAS thickness[24]. In addition, we also measured the length of IAS in the posterior portion of the anal canal in the mid-sagittal plane.…”
Section: Discussionmentioning
confidence: 99%
“…Methods of documenting and reporting of sphincter abnormalities vary in the literature. Some studies record endoanal images at 1 cm levels from the anal verge, 6 while others report the presence of defects in the IAS and EAS within quadrants 13 . Sultan et al .…”
Section: Discussionmentioning
confidence: 99%
“…The mid level of Liverpool Ultrasound Pictorial Chart (LUPIC) is defined as the point at which the EAS joins anteriorly to form a complete ring. As described by Bollard et al , 6 a natural gap or defect occurs in the anterior EAS of many female patients below the level of the puborectalis sling. The exact distance from the anal verge to the LUPIC mid level will therefore vary with this known natural variation in length of the anterior EAS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation